Bitudobe reproduction of typical "Old Adobe" in garden exhibit of California Nursery Company at Golden Gate International Exposition
The picturesque "Old Adobe" on the property of the California Nursery Company at Niles, California, was built as a dwelling about 1853 by the Mexican owners of the property. The thick adobe walls, rough beam supports for the roof, and the quaint interior furnishings are an unfailing source of interest. The reproduction of this ""Old Adobe"" graces the charming garden exhibit of the California Nursery Company on Treasure Island. The 4"x 12"x 18" sun-dried "Bitudobe" bricks were moulded of ordinary clay soil, rendered permanently resistant to moisture by a small proportion of "Bitudobe" Emulsified Asphalt Stabilizer, added while mixing the wet mud.